Information and communication technology for sustainable development - Marolla, Cesar (Boca Raton, FL : CRC Press, 2019)
Information and Communication Technology for Sustainable Development shows how ICT, as an enabler for all spheres of development, can help innovate business processes and operations, and provide faster integration of new technologies into business systems. Focused on sustainability, the book addresses strategic approaches to cope with a range of climatic, environmental, cyber-security threats and other global risks, and aims to promote prosperity and economic growth. Furthermore, it explores how the adoption of new technologies, and collective action based upon a strategic behavioral theory of new leadership, can be applied when responding to specific set of conditions that allow for the proposed strategies to cope with risks. Information technology and strategic planning complement each other to attain the sustainable development goals (SDGs). Risk management frameworks, business continuity systems, and strategic planning methodologies such as mechanism design theory, strategic adaptive cognition (SAC), and risk mechanism theory (RMT) are the fundamental components needed to have a universal approach embedded into the national development plans agenda. As technology no longer follows an orderly, linear path, but improves exponentially, developing a strategic approach to ICT implementation help world leaders in the difficult but inspiring task of making a sustainable world and consequently find solutions to achieve the SDGs and the desired growth pattern that must be sustained, inclusive and equitable. Cesar Marolla is a sustainability and environmental management leader, researcher, author, and lecturer. Throughout his career he has brought strategy concepts to bear on many of the most challenging problems facing corporations and societies and has worked and traveled extensively in Europe, South America, Middle East, Northeast Africa, and the United States. Marolla is the recipient of the 2013 Harvard University Derek Bok Civic Prize Award that recognizes creative initiatives in community service and long-standing records of civic achievement. He is also a graduate of the Executive Program in Sustainability Leadership at Harvard T.H. Chan School of Public Health-- The Center for Health and the Global Environment and a member of the Harvard Advisory Council for the Sustainability Curriculum.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable development -- Information technology; Environmental sciences -- Information technology; COMPUTERS / Computer Engineering; LAW / Environmental; NATURE / Environmental Conservation & Protection